The Impact of Social Media Influencers on Consumer Behavior - Nursansiwi, Dwi Arini (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This study explores the impact of social media influencers on consumer behavior inside the context of digital technology. Through a scientific literature evaluation method, this research investigates different factors that influence influencers have an effect on, including credibility, type of content, social media platform, and level of engagement. The research findings underscore the significance of a deep understanding of the role of influencers in shaping consumer behavior and offer valuable insights for brands and companies in designing powerful advertising strategies.